Challenging the masters of the treaties: Emerging narratives of constituent power in the European Union - PATBERG, MARKUS (Global constitutionalism, 2018)
There is a growing sense that if the EU is to avoid disintegration, it needs a constitutional renewal. However, a reform negotiated between executives will hardly revitalise the European project. In light of this, commentators have suggested that the EU needs a democratic refounding on popular initiative. But that is easier said than done. Shaping the EU has been an elite enterprise for decades and it is hard to imagine how things could be otherwise. In this article, I map four public narratives of constituent power in the EU to sketch out potential alternatives. Political actors increasingly call into question the conventional role of the states as the ‘masters of the treaties’ and construct alternative stories as to who should be in charge of EU constitutional politics, how the respective subject came to find itself in that position, and how it should invoke its founding authority in the future. These public narratives represent a promising starting point for a normative theory that outlines a viable and justifiable path for transforming the EU in a bottom-up mode.